Comparative Study on Production Performance of Different Oat (Avena sativa) Varieties and Soil Physicochemical Properties in Qaidam Basin - Wenqi Wu; Ronglin Ge; Jie Wang; Xiaoli Wei; Yuanyuan Zhao; Xiaojian Pu; Chengti Xu (Plants)
Oats (Avena sativa L.) are forage grasses moderately tolerant to saline-alkali soil and are widely used for the improvement and utilization of saline-alkali land. Using the oat varieties collected from the Qaidam Basin as experimental materials, based on the analysis data of the main agronomic traits, quality, and soil physical and chemical properties of different oat varieties at the harvest stage. The hay yield of Molasses (17,933.33 kg·hm−2) was the highest (p < 0.05), the plant height (113.59 cm) and crude fat (3.02%) of Qinghai 444 were the highest (p < 0.05), the fresh-dry ratio (2.62), crude protein (7.43%), and total salt content in plants (68.33 g·kg−1) of Qingtian No. 1 were the highest (p < 0.05), and the Relative forage value (RFV) of Baler (122.96) was the highest (p < 0.05). In the 0–15 cm and 15–30 cm soil layers of different oat varieties, the contents of pH, EC, total salt, Ca2+, Mg2+, and HCO3− showed a decreasing trend at the harvest stage compared to the seedling stage, while the contents of organic matter, total nitrogen, Cl−, and SO42− showed an increasing trend. The contents of K+ and Na+ maintained a relatively balanced relationship between the seedling stage and the harvest stage in the two soil layers. Qingtian No. 1, Qingyin No. 1, and Molasses all rank among the top three in terms of production performance and soil physical and chemical properties, and they are the oat varieties suitable for cultivation in the research area.